Ingroup identification, identity fusion and the formation of Viking war bands. Issue 1 (1st January 2016) - Raffield, Ben; Greenlow, Claire; Price, Neil; Collard, Mark
Abstract: The lið, a retinue of warriors sworn to a leader, has long been considered one of the basic armed groups of the Viking Age. However, in recent years the study of lið has been eclipsed by the discussion of larger Viking armies. In this paper, we focus on the key question of how loyalty to the lið was achieved. We argue that two processes that have been intensively studied by psychologists and anthropologists – ingroup identification and identity fusion – would have been important in the formation and operation of lið . In support of this hypothesis, we outline archaeological, historical and literary evidence pertaining to material and psychological identities. The construction of such identities, we contend, would have facilitated the formation of cohesive fighting groups and contributed to their success while operating in the field.